INFLUENCE OF SOME CULTURAL PRACTICES ON YIELD, FRUIT QUALITY AND INDIVIDUAL ANTHOCYANINS OF TABLE GRAPE CV. ‘HOROZ KARASI’ - Ö. Kamiloğlu (Journal of Animal and Plant Sciences, 2011)
This study was conducted to determine the effects of different cultural practices on vine yield, bunch and berry characteristics, juice quality, total anthocyanins and individual anthocyanins for ‘Horoz Karası’ table grape which have been demanded in the recent years. In addition to the control vines, seven cultural practices were compared: cluster thinning, boron, topping, cluster thinning + boron, cluster thinning + topping, boron + topping, cluster thinning + boron + topping. The highest and the lowest yields were obtained from boron+topping (14.94 kg vine−1) and cluster thinning (8.58 kg vine−1) practices respectively. For cluster weight and number of berries/cluster; cluster thinning+boron+topping practice yielded the highest value, while cluster thinning practice yielded the lowest value. Total soluble solid (TSS), pH, TSS/acidity characteristics were the highest in cluster thinning practice. It was also determined that such practice increased amounts of total anthocyanin and individual anthocyanins significantly more than other practices. Proportional malvidin-3-glucoside percentage was significantly higher than other individual anthocyanins in this variety. Grape quality and composition were affected by the amount of products in vine. Negative correlations were identified between vine yield and TSS, pH, TSS/acidity, total anthocyanins, Cy-3-G, Dp-3-G, Mv-3-G, Pn-3-G, Pt-3-G.
Keywords: Vitis vinifera L.; table grape; treatment; fruit quality; individual anthocyanins.